The female position and role in Korea and Vietnam (An initial comparison) - Nguyen Thi Thu, Thuy; Le Thi Thanh, Thuy (Adult Education Discourses, 2022)
Society has been continuously changing and developing in various fields, the role and position of women have been increasingly altering and becoming important in society and in family. Korea and Vietnam have the same basic background in terms of Eastern culture and social context. These have strongly influenced gender conception and position. This article analyses the position and role of women in the two countries in the past and present. In order to conduct this research, we applied comparative cultural studies specifically, Affectual/ Consequential comparison, Parallel comparison, Synchronic and Diachronic comparison, Cross-cultural comparison and feminism perspective to highlight the similarities and differences in their position. The findings of the research disclose lots of similarities on the position of women in traditional and modern society as well as reveals no less differences in the assessment of women’s contributions to building and protecting the country, taking care of family and rearing children. Thus, the article will help the audience have a better understanding and knowledge of gender culture in the two countries.